Keberadaan Pendidikan Pondok Pesantren dalam Perkembangan Spritual dan Kultural Masyarakat - Yuldafriyenti; Kamal, Tamrin; Hakim, Rosalawati; Hakim Hanafi, Abdul; Zulhadi (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the role of Islamic boarding school education in the spiritual and cultural development of the community. This research uses a literature method by processing data from literature such as books, articles, and journals. The results of the study show that pesantren are not only the center of religious education but also play a significant role in character formation, tradition preservation, and development of local cultural values. Teaching in pesantren integrates intellectual, spiritual, and social education through the practice of worship, discipline, and social interaction. The flexibility of pesantren is reflected in its adaptation to changing times by combining traditional and modern curricula. With this holistic approach, pesantren helps to produce individuals who are faithful, knowledgeable, and have high social responsibility. In addition, pesantren contribute to the empowerment of the local economy through practical skills training, such as agriculture and crafts. Thus, pesantren remains relevant as an educational institution that supports the spiritual, cultural, and economic development of the community in a sustainable manner.